Unnatural selection - Van Grouw, Katrina, 1965- (Princeton University Press, 2018)
Van Grouw celebrates the 150th anniversary of Charles Darwin's The Variation of Animals and Plants under Domestication, by explaining a previously missing piece to the evolutionary puzzle: the knowledge of how individual traits are passed from one generation to the next. She builds on the analogy that Darwin himself used, comparing the selective breeding process with natural selection in the wild, and features a multitude of examples. In showing that identical traits can occur in all animals, wild and domesticated, and both are governed by the same evolutionary principles, we discover that In wild animals the changes are usually too slow to see; in domesticated animals change happens fast. -- Adapted from Jacket